Answer:
E= 10.2 ev
![Wavelength= 1.21 * 10^(-7) \ m](https://img.qammunity.org/2020/formulas/physics/high-school/x5p11hmbv5rxdo3clvi9a13d57nxcg3m3n.png)
![Frequency =2.479 * 10^(15) \ s^(-1)](https://img.qammunity.org/2020/formulas/physics/high-school/ja34lek0nsr01027knsi3dqn7strcm5t7j.png)
Step-by-step explanation:
It is given that energy in first exited state (n=2) ,
= -3.4 ev
Also , it is given than energy in ground state (n=1) ,
= -13.6 ev.
We know energy of photon released is difference of the final and initial level of electron.
Energy of photon released,
![E=E_(final)-E_(initial)](https://img.qammunity.org/2020/formulas/physics/high-school/bidf5llafg2z0er7txxuermu7uuqbwejaf.png)
Therefore,
.
To convert energy from ev(electron volt) into joule we need to multiply energy in ev by charge of electron which is (
)
Therefore,
![E_(joule) = E_(ev)* 1.6 * 10^(-19) \ joules](https://img.qammunity.org/2020/formulas/physics/high-school/5qw8esguh4b6yfgd88x160uu2b8df0vlax.png)
Now , we know that photon is an quantum of light . Therefore, speed of photon in vaccum is equal to speed of light which is ,
.
Now, by energy-wavelength relation,
![E_(joule)=(h* c)/(\lambda)](https://img.qammunity.org/2020/formulas/physics/high-school/8ku281w58ofa7jbejyd34x24gut7wl5xpf.png)
where ,
![h=6.626* 10^(-34)\ joule-second](https://img.qammunity.org/2020/formulas/physics/high-school/vewq3pwu01gmhaf2g2bhgtf7ty32r89sl5.png)
Now, putting values of h ,c and E in above equation .
![10.2 * 1.6* 10^(-19)=(6.626*10^(-34) * 3 * 10^8)/(\lambda)](https://img.qammunity.org/2020/formulas/physics/high-school/ug5955jfpwx38dhxnrxqw9psq9vkja3syo.png)
![\lambda=\frac{{6.626*10^(-34) * 3 * 10^8}}{10.2 * 1.6* 10^(-19)}](https://img.qammunity.org/2020/formulas/physics/high-school/mz9pzhmgkvck0z368ktunyls8eay9rt6wr.png)
![\lambda=1.21 * 10^(-7)\ m](https://img.qammunity.org/2020/formulas/physics/high-school/7lqgbvjuckh7e6lomsa6lyt4c746ynvxjs.png)
We know,
![c=\lambda* frequency](https://img.qammunity.org/2020/formulas/physics/high-school/gu5h85trv0bf0vepr82jv1ksjuo6abb49e.png)
Therefore,
![frequency=(c)/(\lambda)= (3* 10^8)/(1.21* 10^-7) \ s^(-1)=2.479* 10^(15) \ s^(-1)](https://img.qammunity.org/2020/formulas/physics/high-school/q95ufv1rapxjq6laj4rmwzfi5rj080j60o.png)
Hence, this is the required solution.